2015
DOI: 10.1177/0022022115588950
|View full text |Cite
|
Sign up to set email alerts
|

Do Cultural Values Matter? A Cross-Cultural Study of the Third-Person Effect and Support for the Regulation of Violent Video Games

Abstract: This article aims to extend third-person effect research into a cross-cultural context. How and why the third-person perception (perceptual gaps between media effect on self and others) has dissimilar association with the willingness to support regulation of media content in the United States and South Korea is investigated. The survey results demonstrate a larger third-person perception among U.S. respondents than among Korean respondents. Regression and mediation analyses reveal that the different levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…Beyond theoretical models, different factors have been advanced in support of the perceptual component, such as gender and race (David et al, 2002; Lo and Wei, 2002), religiosity (Golan, 2002), education (Peiser and Peter, 2000), the social distance (Jensen and Hurley, 2005), the cultural mores (Lee and Tamborini, 2005) and values (Hong, 2015), and so on. In what concerns education, most studies suggest that better educated people tend to show stronger third person perception (Salwen, 1998; Tiedge et al, 1991), since they tend to consider themselves more knowledgeable, if not generally superior, than others, and to approach media messages more cautiously.…”
Section: The Third Person Effect: Components and Predictorsmentioning
confidence: 99%
“…Beyond theoretical models, different factors have been advanced in support of the perceptual component, such as gender and race (David et al, 2002; Lo and Wei, 2002), religiosity (Golan, 2002), education (Peiser and Peter, 2000), the social distance (Jensen and Hurley, 2005), the cultural mores (Lee and Tamborini, 2005) and values (Hong, 2015), and so on. In what concerns education, most studies suggest that better educated people tend to show stronger third person perception (Salwen, 1998; Tiedge et al, 1991), since they tend to consider themselves more knowledgeable, if not generally superior, than others, and to approach media messages more cautiously.…”
Section: The Third Person Effect: Components and Predictorsmentioning
confidence: 99%
“…Similarly, Greece has been defined as being more horizontally collectivistic than Cyprus (likely due to Cyprus’ exposure to the British Commonwealth; Stavropoulos et al, 2018a ). Such differences in cultural features have been shown to associate with online behaviors in general and gaming involvement patterns in particular ( Lee and Wohn, 2012 ; Xu-Priour et al, 2014 ; Hong, 2015 ) and to impact the psychometric equivalence of measures ( Stavropoulos et al, 2017b ). For instance, findings from a measurement invariance (MI) study of the Internet Gaming Disorder Scale – Short Form 9 between the United States, the United Kingdom, and India revealed that despite cross-country consensus of a one-factor structure of the instrument, there were cross-country differences on the metric and scalar level of analyses ( Pontes et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Detenber and Rosenthal [16] found more support for media censorship and bigger social pressure to conform in a collectivist society than in an individualistic society. After measured COL and IND scores in Korea and the United States, Hong [17] noted IND as a factor of the third-person perception, while COL significantly predicted a positive support for regulating violent video games. Namely, IND and COL work differently at the perceptual levels and the behavioral levels of the third-person effect.…”
Section: Corrective Actions As the Third Person Effectsmentioning
confidence: 99%
“…In this vein, the UA's role in estimating the media's effect on others associates with restrictive behaviors. In a research, Hong [17] found that the UA also contributed to a higher level of consents to media regulation. It is important to consider two behaviors of third-person perceptions in terms of fake news on global warming: restriction of fake news distribution and support for donations to decrease global warming and its education.…”
Section: Corrective Actions In the Cross-cultural Contextmentioning
confidence: 99%
See 1 more Smart Citation